Strategi Up Selling di Hotel XXX Nusa Dua - Prananta, I Komang Yoga; Indrayani , I Gusti Ayu Putu Wita; Iswarini, Ni Ketut (Journal of Hospitality Accommodation Management (JHAM), 2024)
The purpose of this study is to determine the up-selling strategies how receptionists implement up-selling strategies. This research is important to increase the revenue of hotel XXX Nusa Dua.. The data analysis technique used in this research is qualitative descriptive, and the discussion of this research refers to the theory of steps in up-selling by Sanjiwani (2023). The analysis results show that there are similarities and differences between the theory and the actual implementation. The similarity is that receptionists can explain the benefits of products with higher value. On the other hand, the criteria that are not met are that receptionists are unable to analyze guests' needs, do not offer the most expensive products, and do not provide discounts or special prices. Based on these results, the suggestions that can be given are that receptionists should improve their ability to analyze guest characteristics, be more proactive in offering products with the highest price, and the management should conduct more frequent training related to up-selling.